WT1 influences apoptosis and proliferation of immature mice granular cells through regulation of the wnt/Î²-catenin signal pathway - Wang, Juan; Qiu, Jianping; Bo, Le; Wu, Zhinan; Zhou, Anwen; Xu, Wendan; Mao, Caiping (Cellular and Molecular Biology, 2019)
It was to study the influence of Wilms tumor suppressor gene (WT1) on ovarian granular cells (GCs) in mice, and the molecular mechanism involved. LV-WT1 short hairpin ribonucleic acid (shRNA) vector was used to downregulate WT1 expression in granular cells (GCs). The effects of WTI on proliferation and apoptosis of GCs were investigated. Western blot and qRT-PCR were used to assay the mRNA and protein expressions of Bax/bcl-2 in GCs transfected with LV-WT1-RNAi. The expression levels of SUZ12, Wnt5a, Wnt11, Wnt4, Wnt3a, Wnt2 mRNA in GCs were also determined. LV-WT1-RNAi significantly reduced WT1 expression, increased apoptosis and inhibited proliferation of GCs. The inhibition of WT1 had no significant effect on the expression of bcl-2 in GCs. The expressions of Wnt2, Wnt4 and Wnt5a were augmented in WT1-knockdown GCs, relative to non-transfected cells. WT1 activation is necessary for maintaining early survival of GCs in follicles via activation of the Wnt/Î²-catenin signal pathway.